Genetically Yours: Bioinforming, Biopharming, and Biofarming - Hwa A Lim (World Scientific, 2002)
This study covers key aspects in the field of biotechnology, with topics such as genome projects, animal and human cloning, and biowarfare. The author presents firsthand accounts from both the scientific and the business perspective. Each chapter is self-contained and there are footnotes